Investigation into the prevalence, spinal kinematics and management of adolescent male rowers with low back pain - Ng, Leo (Curtin University, 2013)
This thesis investigated back pain in adolescent rowers. A high prevalence of low back pain was found in adolescent male rowers. Differences in lumbar spine movement patterns during ergometer rowing were observed between genders and in adolescent males with back pain compared to those without. A cognitive functional intervention was tested in a randomized controlled trial and was demonstrated to reduce pain and disability, improve muscle endurance and alter sitting spinal postures in adolescent male rowers.